1996
DOI: 10.1074/jbc.271.45.28502
|View full text |Cite
|
Sign up to set email alerts
|

Cysteines 153 and 154 of Transmembrane Transforming Growth Factor-α Are Palmitoylated and Mediate Cytoplasmic Protein Association

Abstract: Transforming growth factor-␣ (TGF-␣) is synthesized as a transmembrane protein with a highly conserved, short cytoplasmic domain that is rich in cysteines. TGF-␣ is a prototype of a large family of growth factors involved in cell-cell communication. We have shown previously that transmembrane TGF-␣ associates with a kinase activity and two proteins of 106 and 86 kDa. In this study, we have used site-directed mutagenesis of the cytoplasmic domain of TGF-␣ to define the structural requirements for these protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 60 publications
0
37
0
Order By: Relevance
“…The attached lipid functions either as a mediator of membrane association or as a determinant for speci®c protein-protein interactions (Casey and Seabra, 1996;Zhang and Casey, 1996). Immunoprecipitation using an antibody raised against the carboxyl-terminal peptide of wt TGF-a identi®ed the association of a kinase protein p86 with the cytoplasmic tail of the TGF-a precursor, in CHO cells overexpressing wt TGF-a (Shum et al, 1996). This association required palmitoylation of cysteines 153 and 154.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The attached lipid functions either as a mediator of membrane association or as a determinant for speci®c protein-protein interactions (Casey and Seabra, 1996;Zhang and Casey, 1996). Immunoprecipitation using an antibody raised against the carboxyl-terminal peptide of wt TGF-a identi®ed the association of a kinase protein p86 with the cytoplasmic tail of the TGF-a precursor, in CHO cells overexpressing wt TGF-a (Shum et al, 1996). This association required palmitoylation of cysteines 153 and 154.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recently it was demonstrated that the carboxyl-terminal valine residues of proTGF-a are required for its e cient maturation, rather than for proteolytic processing (Briley et al, 1997). The cytoplasmic region is highly conserved among di erent species, and does not contain any obvious enzymatic motifs (Shum et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Deleting the C-terminal ETVV and mutating two separate dicysteines (CC3SS) did not affect the interaction with NKD2. Thus, binding of TCT to NKD2 does not require the PDZ target motif or palmitoylation of the tail, which occurs on cysteine residues 153 and 154 (14). Replacing the middle region of TCT with the cytoplasmic domain of AR (TGF␣3AR), an EGFR ligand that also is sorted to the basolateral surface of polarized epithelial cells (3), eliminated NKD2 binding.…”
Section: Nkd2mentioning
confidence: 99%
“…The carboxyl-terminal valine residue is important for intracellular tracking and maturation of the TGF-a precursor (Briley et al, 1997;Urena et al, 1999). The cytoplasmic tail of the wild type TGF-a precursor (WT) has also been reported to physically associate with a protein complex possessing both tyrosine kinase and serine/threonine kinase activity (Shum et al, 1994(Shum et al, , 1996. This association suggests that WT TGF-a precursor may have a signaling function.…”
Section: Introductionmentioning
confidence: 99%